Spectrophotometric Determination of Ascorbic Acid with Hemoglobin as Catalyst - Li, Qiang; Li, Yu; Lin, Cuiping; Shi, Jie; Wang, Ruiyong (Asian Journal of Chemistry, 2014)
A novel method was described for the determination of ascorbic acid based on the catalytic effect of hemoglobin for the oxidation of hydrogen peroxide and o-phenylenediamine. UV-visible spectrophotometry was used to study the kinetic behaviour of the oxidation reaction. The optimal conditions of the system were found. A linear calibration graph was obtained over the ascorbic acid concentration range of 1.0 × 10-9 – 2 × 10-8 mol/L with a correlation coefficient of 0.9996. The results confirmed that the absorbance of the catalytic system can be enhanced obviously in the presence of limited ascorbic acid and the detection method of ascorbic acid with hemoglobin as catalyst is feasible.